Ideology and Holy Landscape in the Baltic Crusades. - Leighton, Gregory (Amsterdam : Arc Humanities Press, 2022)
This book examines how the military orders and the ideology of crusading gave rise to a new sacred landscape in the medieval Baltic region, an outpost of Latin Christianity.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books